Nutrition economics principles and policy applications - Babu, Suresh Chandra; Gajanan, Shailendra N.; Hallam, J. Arne (Academic Press, an imprint of Elsevier, 2017)
"Nutrition Economics: Principles and Policy Applications establishes the core criteria for consideration as new policies and regulations are developed, including application-based principles that ensure practical, effective implementation of policy. From the economic contribution of nutrition on quality of life, to the costs of malnutrition on society from both an individual and governmental level, this book guides the reader through the factors that can determine the success or failure of a nutrition policy." --publisher's website.